Coronavirus, the great toilet paper panic and civilisation. (August 2021) - Stratton, Jon
Panic buying of toilet rolls in Australia began in early March 2020. This was related to the realisation that the novel coronavirus was spreading across the country. To the general population the impact of the virus was unknown. Gradually the federal government started closing the country's borders. The panic buying of toilet rolls was not unique to Australia. It happened across all societies that used toilet paper rather than water to clean after defecation and urination. However, research suggests that the panic buying was most extreme in Australia. This article argues that the panic buying was closely linked to everyday notions of Western civilisation. Pedestal toilets and toilet paper are key aspects of civilisation and the fear of the loss of toilet paper is connected to anxiety about social breakdown, the loss of civilisation. This is the fear manifested in the perceived threat posed by the virus.